Wolbachia-based biocontrol for dengue reduction using dynamic optimization approach (2020)
Aedes aegypti females mosquitoes are the principal transmitters of dengue and other arboviral infections. In recent years, it was disclosed that, when deliberately infected with Wolbachia symbiont, this mosquito species loses its vectorial competence and becomes less capable of transmitting the virus to human hosts. Thanks to this important discovery, Wolbachia-based biocontrol is now accepted as an ecologically friendly and potentially cost-effective method for prevention and control of dengue and other arboviral infections. In this paper, we propose a dengue transmission model that accounts for the presence of wild Aedes aegypti females and those deliberately infected with wMelPop Wolbachia strain, which is regarded as the best blocker of dengue and other arboviral infections. However, wMelPop strain of Wolbachia considerably reduces the individual fitness of mosquitoes, what makes rather challenging to achieve the gradual extrusion of wild mosquitoes and ensure their posterior replacement by Wolbachia-carriers. Nonetheless, this obstacle have been overcome by employing the optimal control approach for design of specific intervention programs based on daily releases of Wolbachia-carrying mosquitoes. The resulting optimal release programs ensure the population replacement and eventual local extinction of wild mosquitoes in the finite time and also entail a significant reduction in the number of expected dengue infections among human hosts under the long-term settings